Treatment-Resistant Blunted HPA Activity, but Reversible Cardiovascular Stress Reactivity in Young Women With Eating Disorders - Het, Serkan; Vocks, Silja; Wolf, Jutta M.; Herpertz, Stephan; Wolf, Oliver T. (Frontiers in Psychiatry, 2020)
Previous research has provided evidence for a reduced neuroendocrine stress response in women with eating disorders (EDs). In the present study female in-patients with Anorexia and Bulimia nervosa were compared to female healthy controls (HC) before and after completing an in-patient treatment program. Salivary cortisol, alpha-amylase (sAA), heart rate response (HR), high-frequency heart rate variability (HF-HRV) and negative affective state were measured before, during and after exposure to the Trier Social Stress Test (TSST) at pre- and post-treatment. Patients with EDs (n =13) showed significantly less ED symptoms at post-treatment. Compared to HC (n = 22), patients displayed a blunted cortisol stress response combined with overall attenuated sAA levels at pre-treatment. At post-treatment, the blunted cortisol stress response was still observable, while the differences in sAA responses disappeared. HR was attenuated at pre-treatment in patients, also indicated by a stronger HF-HRV throughout the TSST. These cardiovascular differences disappeared at post-treatment. Patients reported in general (pre- and post-treatment) more negative affect compared to HC. This study provides further evidences of a hypo-reactive Hypothalamus-pituitary-adrenal axis (HPA) in patients with EDs which persists even after symptom recovery while initial low cardiovascular stress reactivity apparently can be restored by psychotherapy. Given the small sample size the findings have to be considered preliminary.